1994
DOI: 10.1161/01.cir.90.2.746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thrombolytic therapy administered 6 to 24 hours after myocardial infarction on the signal-averaged ECG. Results of a multicenter randomized trial. LATE Ancillary Study Investigators. Late Assessment of Thrombolytic Efficacy.

Abstract: Late thrombolytic therapy produced a more stable electrical substrate, which probably represents an important mechanism of mortality benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…A meta-analysis of all available prospective studies, during the pre-thrombolytic era, on the use of SAECG after myocardial infarction showed that the SAECG predicted a sixfold increase in risk of arrhythmic events independent of left ventricular function, and an eightfold increase in risk of arrhythmic events independent of Holter results [91] . Thrombolysis reduced the frequency of SAECG abnormalities by 37% [92] and, in this setting, the predictive value of late potential was diminished [93] . More recent studies supported the concept that SAECG is an independent predictor of arrhythmic events after MI [86,93,94] .…”
Section: Late Potentialsmentioning
confidence: 67%
“…A meta-analysis of all available prospective studies, during the pre-thrombolytic era, on the use of SAECG after myocardial infarction showed that the SAECG predicted a sixfold increase in risk of arrhythmic events independent of left ventricular function, and an eightfold increase in risk of arrhythmic events independent of Holter results [91] . Thrombolysis reduced the frequency of SAECG abnormalities by 37% [92] and, in this setting, the predictive value of late potential was diminished [93] . More recent studies supported the concept that SAECG is an independent predictor of arrhythmic events after MI [86,93,94] .…”
Section: Late Potentialsmentioning
confidence: 67%
“…Thus, thrombolytic therapy reduces the incidence of an abnormal SAECG in MI survivors. [91][92][93][94] SAECG performed early after MI is abnormal in 15% to 35% of patients. SCD or cardiac arrest occurs in 3.3% to 9% of these patients over the following 1 to 3 years.…”
Section: Signal-averaged Ecgmentioning
confidence: 99%
“…[12][13][14] Moreover, it has been proposed that an open artery may increase tolerance to future coronary events and provide electric stability. 15,16 Previous studies with ICD recipients have focused on global coronary artery disease, with no difference between CTO or non-CTO arteries. With an increase in the number of ICD implantations for ischemic cardiomyopathy, a great number of patients with CTO can be expected.…”
Section: Clinical Perspective On P 154mentioning
confidence: 99%